2002
DOI: 10.1046/j.0028-646x.2001.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizas increase apoplastic water transport and root hydraulic conductivity in Ulmus americana seedlings

Abstract: Summary• The extent to which water channel transport is responsible for the observed increases in root water flow of ectomycorrhizal plants is reported here.• To examine the contribution of water channel transport to root hydraulic conductance, temperatures in the range 4 -20 ° C and mercuric chloride (HgCl 2 ) were used to study the kinetics of water transport in ectomycorrhizal and nonmycorrhizal roots of American elm ( Ulmus americana ) seedlings.• Hydraulic conductance declined with decreasing temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 35 publications
3
49
0
1
Order By: Relevance
“…2b1) despite their similar leaf Ψ (Fig. 2a1, 2a2), suggesting an improved hydraulic conductance in mycorrhizal plants (Mushin and Zwiazek, 2002). Moreover, Garmendia et al (2005) measured higher pressure potential (Ψ p ) in leaves of mycorrhizal pepper compared to that found in nonmycorrhizal plants, which may be due to different wall elasticity in the leaf cells from the two types of plants.…”
Section: Leavesmentioning
confidence: 90%
“…2b1) despite their similar leaf Ψ (Fig. 2a1, 2a2), suggesting an improved hydraulic conductance in mycorrhizal plants (Mushin and Zwiazek, 2002). Moreover, Garmendia et al (2005) measured higher pressure potential (Ψ p ) in leaves of mycorrhizal pepper compared to that found in nonmycorrhizal plants, which may be due to different wall elasticity in the leaf cells from the two types of plants.…”
Section: Leavesmentioning
confidence: 90%
“…In a few studies, ectomycorrhizas have been found to increase hydraulic conductance of tree roots (e.g. [29,34]); whereas other authors reported negative or neutral effects [31]. An only limited effect on water uptake would be understandable because mycorrhizae affect the outer part of the root rather than the stele and endodermis which, for geometric and other reasons, may represent the bottle neck.…”
Section: Discussionmentioning
confidence: 99%
“…almeriense M plants subjected to drought stress presented a higher colonization percentage than in watered plants, confirming that this symbiosis is responsive to drought stress, which modifies not only the total colonization of roots but also the main type of mycorrhization. Fungal hyphae of ectomycorrhiza do not penetrate the cell wall of the root and, therefore, one way of increasing hydraulic conductance in roots is by decreasing the water flow resistance of the apoplastic pathway (Muhsin and Zwiazek 2002). However, apoplastic water flow in roots is restricted by the presence of suberized barriers such as the exo-or endodermis and water is then forced to follow the cell-to-cell pathway (symplastic and transmembrane) (Steudle and Peterson 1998).…”
Section: Discussionmentioning
confidence: 99%